Planar 2-Degrees Of Freedom Underactuated Manipulator: Design And Control - Dwaik, Mohammad; Alsarsour, Maher; Karaki, Ayman (جامعة بوليتكنك فلسطين - ميكانيك, 2021)
يهدف هذا المشروع الى تصميم وبناء و التحكم بذراع آلي افقي ثنائي درجات الحرية غير كامل الدفع)عدد المحركات اقل من عدد درجات الحرية( .هذا الذراع مهم و تمت دراسته و عرضه و تحليله حسب استراتيجيات التحكم المستخدمة في الدراسات السابقة . تم اشتقاق و تحليل نموذج ديناميكي كامل للذراع ، و بنيت عدة تقنيات تحكم على اساس هذا النموذج على التطبيق العملي للذراع الذي أنشئ في هذا المشروع . تقسم استراتيجية التحكم بالذراع الى قسمين ، االول يكون بالتحكم بالذراع ثنائي درجات الحرية باستعمال التقنيات المقترحة ، والثاني يكون بإيجاد عالقة بين زوايا الذراع و بذلك يتحول الى احادي درجة الحرية ويتحكم به على هذا االساس . This project aims to design, control and implement a planar two degrees of freedom (2DOF) underactuated manipulator. This robot is important and had been studied in the literature which reviewed and analyzed it based on the used control strategy. A full dynamic model of this type of robot is derived and analyzed, several control approaches based on this model have been implemented on an experimental setup that has been designed and implemented in this project. The strategies of the control are divided into two parts, the first is by controlling the 2 DOF underactuated manipulator using the suggested control methods, and the other is finding a relation between the joint angles to convert the 2 DOF manipulator to 1 DOF manipulator then controlling it. Keywords: underactuated, two link, planar, position control
Design And Control
no of pages 134, ميكانيك 5/2021
Keywords: Planar 2 Degrees Of Freedom Underactuated Manipulator